Designing front-of-pack labels for packaged food in low-literacy contexts: Consumer perspectives from India - Lakshmi K. Josyula; Simone Pettigrew; Palak Mahajan; Claire Johnson; Devarsetty Praveen; Rachita Gupta (PLOS Global Public Health, 2026)
Front-of-pack labels (FoPLs) on food products are an evidenced-based, effective strategy to raise consumer awareness of the composition and (un)healthiness of packaged foods and help consumers make informed food choices. We undertook a community-based study, in two regions in India, to understand food purchasing patterns and the essential content and design of an effective and contextually acceptable FoPL, and to gather consumer input on a draft FoPL developed by the Food Safety and Standards Authority of India. We conducted 16 focus group discussions with 112 adults, who were regular grocery shoppers for their families. Participants were selected purposively for diversity in gender, educational attainment, socioeconomic status (SES), and site of residence. Data were analysed thematically. Nutrition literacy was revealed to be quite low in most participants, particularly those with low educational attainment, and of low SES. Purchases of packaged foods, including snacks, beverages, and ready-to-eat meal components, were reported to be guided by habit, trust, taste, and others’ recommendations. Nutrition information influenced food purchasing decisions mostly for those following diets for various health conditions. Nutrition information on products, although desired, was not always understood correctly. Symbols without supporting text were sometimes interpreted incorrectly. Interpretive FoPLs with clear, readable text, and colours were preferred, and almost all participants wanted FoPLs to be mandatory. A robust nutrition literacy campaign is essential to set the stage for, and accompany the effective implementation of, an FoPL. An ideal FoPL for India would be mandatory, provide nutrition facts, and also interpret them in a summary format for consumers’ benefit. Information in languages suitable for the diverse population combined with colours and symbols would enhance the utility of the FoPL.